Honeysuckle summer - Woods, Sherryl (Don Mills, Ont. : MIRA, 2010)
Shielded from the world by her best friends, the Sweet Magnolias, Raylene Hammond, recovering from a disastrous marriage, meets and falls in love with sheriff's deputy Carter Rollins, but wonders if she's strong enough to accept what he is offering.
Contains a readers' guide.
Keywords: Female friendship -- Fiction; Divorced women -- Fiction; Sheriffs -- Fiction; South Carolina -- Fiction; Love stories